Magnetic interactions and spin-wave stiffness constant of In-substituted yttrium iron garnets - Huong, Vu Thi Hoai (H. : ĐHQGHN, 2020)
Indium-substituted yttrium iron garnet samples, Y3Fe5 xInxO12 (x ¼ 0e0.7, step 0.1), were prepared using a citrate solgel method. Synchrotron X-ray diffraction (SXRD) measurements combined with the Rietveld refinement technique were used to investigate the crystallization, structure parameters and lattice distortion in the samples. Magnetization and Curie temperature of the samples were measured with the SQUID and VSM equipments. The non-magnetic indium ions were found to reside at the octahedral sites, leading to an increase of the total magnetization and a decrease in the Curie temperature. Molecular field coefficients Naa, Ndd and Nad were determined by fitting the experimental thermomagnetization curves in the framework of a two-sublattice ferrimagnetic model. The stiffness constant of the spin waves, D, in these samples was calculated based on the exchange interaction constants, Jij, and its temperature dependence was derived for the sublattice magetizations. The calculated results for D(T) are in good agreement with the experimentally measured data and are significantly large around room temperature.